Grammatical Orientation of Quranic Readings according to Sibawayh in Al Kitaab and Its Explanations - Hussein, Basim Salih; Majeed, Ali Jadullah (Journal of Tikrit University for Humanities, 2020)
This research deals with the phenomenon of Grammatical Orientation of Quranic Readings according to Sibawayh in the Book and Its Explanations. The researchers have investigated the situation in which Sibawayh has oriented the Quranic Readings based upon his own linguistic sense and what is written by the interpreters after him. It proves that Sibawayh has cited The Holy Quran and its readings in many of grammatical rules. Furthermore, he grammatically oriented some the readings depending upon prosaic and metrical speech orally narrated among Arabs. Those who are concerned with the explanation of Al Kitab have done the same. Their approach has two aspects: firstly, what they have mentioned based on Sibawayh’s book and secondly their stated readings with grammatical justification or an earlier mentioned viewpoint.